Factors Affecting the Implementation of Green Tourism in Da Nang City - Trinh Le Tan; Ngo Cat Tuong; Phan Hai Nguyet; Luu Minh Man; Hoang Thi Lan Nhi; Nguyen Thao Van (International Journal of Community Service & Engagement, 2021)
This article describes the impact of factors affecting the implementation of Green Tourism as a sustainable tourism type in Da Nang City after the Covid-19 pandemic and in the near future. Today, air pollution and the Covid-19 pandemic are urgent problems that people are facing to overcome and stabilize social life as well as the economy. With the title of Vietnam's National Green City (Danang city's e-portal, 2018), Da Nang - one of the most famous tourist cities in Vietnam, has many favorable conditions for the development of the “green tourism” model, contributing to the development of a sustainable green economy. We use qualitative research to establish the hypotheses in this research. In the quantitative research, data were collected from business owners dealing in accommodation and travel services in the tourism industry in Da Nang city through questionnaires. The data analysis methods used in this study are Cronbach and EFA methods, correlation, and regression. The results show that there are 4 factors: Cost, Green Awareness, Competitive Advantages, and Policy of Government affecting the implementation of the green tourism model in Da Nang. Most of the business owners providing accommodation and travel services in the tourism industry in Da Nang city are aware of the importance and potential of developing "green tourism" in Da Nang in the future.